A Study on Different Web Service Discovery Approaches - Mirajkar, Rahul P; Karande, Nikhil D; Yadav, Surendra (International Journal of Computer Sciences and Engineering, 2018)
A web service is a software system designed to support interoperable machine-to-machine interaction over a network. In today’s date, web services are becoming widespread to utilize the web as a business opportunity for offering their own services and using existing services from others. A web service is a service offered by an electronic device to another electronic device, communicating with each other via the World Wide Web. A web service registry UDDI (Universal Description, Discovery, and Integration) provides interoperable, standards based approach for methodically documenting and publishing web services. Since various services are available, it becomes difficult to find the most appropriate service for an exact application. Faced with the increasing numbers of Web services and service users, researchers in the services computing field have attempted to address a challenging issue, i.e. how to quickly find the suitable ones according to user queries. Many previous studies have been reported towards this direction. This paper presents a study on different web service discovery approaches.